Methodology for calculating rate by concept of surveillance and special tax of ports and transport superintendence (2016)
Through this, it is to publicize and over the years has made the calculation for the charging rate monitoring, today special contribution, since the beginning of the Superintendent of Ports (1991) to the date, called Superintendency of Ports and Transport; turn and what are the factors that have influenced entities determining the percentage to pay for each monitored, according to the service provided.